The cognitive impact on innovative thinking to increase brainstorming for fifth preparatory students in drawing (Journal of the College of Basic Education, 2023)
Arts in general expand the imagination of students, through which they learn how to express their ideas and visions freely and fluently. The ways of expression may vary from one person to another. Some people communicate with the other through drawing, others see music as a source for generating feelings and feelings, and a third group resort to the art of theater or writing poetry. All these expressions enable the student to rise and rise, develop his behavior and enhance his activities in changing the lifestyle he lives for the better. Artistic and aesthetic education also has various roles that work to organize the life of the individual, and they are represented in the educational role as well as entertainment, as well as emotional as well as social. We are currently living in the present time and we see the era of globalization and informatics in education and in various fields of life, it is the era of third technology, it is an era characterized by continuous change and acceleration and openness to the cultural and civilized media openness, and with this revolution the increasing realization that the issue is not any education provided, but what is required is an education that achieves for the learner. The data and skills he needs, to be able to use the thinking processes, to face the problems that can challenge him, and the obstacles that stand in the way, and to employ knowledge and harness it to serve the community. Education today has become an education for the development of thinking.This research seeks to show the extent of the cognitive impact on innovative thinking to increase brainstorming for fifth preparatory students through the subject of drawing, with an indication of what this requires in developing the skills of students and teachers, and the need to provide the appropriate atmosphere by the school